2022
DOI: 10.3390/ijms231810224
|View full text |Cite
|
Sign up to set email alerts
|

ZBP1: A Powerful Innate Immune Sensor and Double-Edged Sword in Host Immunity

Abstract: Z-conformation nucleic acid binding protein 1 (ZBP1), a powerful innate immune sensor, has been identified as the important signaling initiation factor in innate immune response and the multiple inflammatory cell death known as PANoptosis. The initiation of ZBP1 signaling requires recognition of left-handed double-helix Z-nucleic acid (includes Z-DNA and Z-RNA) and subsequent signaling transduction depends on the interaction between ZBP1 and its adapter proteins, such as TANK-binding kinase 1 (TBK1), interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 191 publications
(319 reference statements)
2
21
0
Order By: Relevance
“…ZBP1 was originally identified as an innate immune sensor that activates interferon (IFN) responses and NF-κB signaling (43). Recently, ZBP1 has been reported as the master protein inducing PANoptosis (pyroptosis, apoptosis, and necroptosis) (29). Our past and present results confirmed that ZBP1 expression was upregulated in host macrophages upon ASFV infection (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…ZBP1 was originally identified as an innate immune sensor that activates interferon (IFN) responses and NF-κB signaling (43). Recently, ZBP1 has been reported as the master protein inducing PANoptosis (pyroptosis, apoptosis, and necroptosis) (29). Our past and present results confirmed that ZBP1 expression was upregulated in host macrophages upon ASFV infection (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…The Zα domain of ZBP1 is important for sensing accumulated Z-NA and its nuclear migration (29,30). By reconstituting the Myc-tagged ZBP1 mutant plasmid lacking the Zα2 domain (Myc-ZBP1 ΔZα2 ) that based on the Myc-tagged porcine wild-type ZBP1 plasmid (Myc-ZBP1 WT ) (Fig.…”
Section: Z-dna Form and Are Recognized By Zbp1 In Asfv-infected Pamsmentioning
confidence: 99%
“…Despite decades of research, structural information on, and the biological relevance of, Z-RNA are still lacking. Very recently, several seminal studies have revealed the intriguing function of Z-RNA as a pathogenic factor and demonstrated the importance of the Z-RNA-binding protein, which initiates an immune response in vivo. These reports shed new light on Z-helix, Z-RNA/Z-DNA-binding domain-containing proteins, and their biological significance in gene regulation, innate immunity, and cancer diseases. Our group has been interested in Z-DNA/Z-RNA and has developed useful fluorescent nucleosides to detect the B–Z transition of DNA/RNA to investigate their interactions with proteins. , We have also developed a versatile nucleic acid-based FRET system that affords vivid fluorescence changes via a B–Z transition .…”
Section: Results and Discussionmentioning
confidence: 99%
“…As a newly discovered programmed cell death mode, PANoptosis participates in fine-tuning anti-tumor immunity in TME by regulating the enrichment of immune cells and accelerating the death of tumor cells ( Hao et al, 2022 ; Liu et al, 2022 ). Only a few malignant tumors in advanced LIHC can be completely removed by surgery.…”
Section: Discussionmentioning
confidence: 99%